Expressions of angiogenic markers and apoptotic markers in soft tissue sarcoma - Yusuf, Yusri (2010)
Introduction: For tumor development and progression, angiogenesis and apoptosis play a crucial role. No study so far has tried to associate these two activities in tumor cells as well as correlation of both activities in the tumor and the endothelial cells. Conclusion: This study supports the role of endothelial cells in survival and regression of tumor cells in tumoregenesis. Thus, the inhibition of endothelial cells survival factor or activation ofendothelial cells death is a promising prospect as a candidate for tumor therapy. All the proteins used in this study might be potential as a useful marker for diagnosis of specific histologic subtypes especially Bcl-2 since there is diversity in expression amongst the various histologic subtypes in STS. An increase in angiogenic activity may inhibit apoptotic tumor cells death which leads to cell proliferation. However, the angiogenic activity was independent of anti-‐apoptotic activities. A better understanding of their relations probably provides the basis for more rational cancer therapies in the future.